European entrepreneurship research and practice : a multifaceted effort towards integration of different perspectives - Raith, Matthias; Songini, Lucrezia; Starnawska, Marzena; Pellegrini, Massimiliano M.; Gnan, Luca; Lundberg, Hans (College teacher) (Emerald Publishing Limited : Information Age Publishing, inc., 2020)
"The tradition of European scholars on entrepreneurship has been consolidated during the last three decades and an increasingly distinct European school of thought has emerged as a consequence. This development provides as solid base for the future development of the field where Europe and its entrepreneurship scholars will play an increasingly prominent role in the development of the field. The distinct focus of the book is key European features - 'contexts matter' - to promote and stimulate what 'European' might mean in any given context. The book valorizes different contexts and key strengths of the European perspective"-- Provided by publisher.
Keywords: Entrepreneurship -- Europe -- Case studies.; Minority business enterprises -- Europe.; Business networks -- Europe.; Organizational change -- Europe.; elektronické knihy; Case studies.; Business & Economics -- Entrepreneurship.; Entrepreneurship, Start-ups.; electronic books